PENGARUH KEPEMILIKAN, RASIO KEUANGAN DAN TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA - Umar Issa Zubaidi; Veronica Angela (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research was to determine the effect of managerial ownership, institutional ownership, firm size, leverage, profitability, sales growth, director size, and independent commissioners on earnings management. That’s mean in this research have eight independent variable which have influence (or not) on earnings management. This research uses 177 non-financial companies listed in Indonesia Stock Exchange from 2018 until 2020. The sample selection technique in this research is purposive sampling and uses secondary data obtained from the official website of Indonesia Stock Exchange and company website. The data are tested and analysed using multiple regression method. The results of this research indicate that firm size and independent commissioners has negative influence on earnings management and profitability has positive influence on earnings management. While, managerial ownership, institutional ownership, leverage, growth, and director size have no influence on earnings management